AI in Education: Shaping the Future of Teaching and Learning - James P. Takona (International Journal of Current Educational Studies)
This study examines the impactful incorporation of Artificial Intelligence (AI) in higher education, emphasizing its ability to improve teaching methods, simplify administration, and facilitate individualized learning. By analyzing literature and assessing case studies, this study demonstrates how AI promotes creativity, enhances critical thinking, and provides personalized learning experiences. Moreover, AI streamlines repetitive tasks like scheduling and communication, allowing educators to concentrate on impactful student interaction and instructional creativity. Nonetheless, the research also highlights significant challenges, including ethical worries regarding data privacy and algorithmic bias, issues of equity such as the digital divide, and the dangers of reduced human interaction. Tackling these challenges necessitates careful design and teamwork to guarantee that the incorporation of AI is in harmony with educational principles. The results indicate that, if applied thoughtfully, AI has the potential to transform higher education into a more adaptive, inclusive, and effective system, aligning technological advancements with the fundamental goal of promoting fair and significant learning opportunities.